If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
2*x-((2*y)/3) = 6 // - 6
2*x-((2*y)/3)-6 = 0
2*x+(-2/3)*y-6 = 0
2*x-2/3*y-6 = 0 // + -2/3*y-6
2*x = -(-2/3*y-6) // : 2
x = (-(-2/3*y-6))/2
x = (6-(-2/3*y))/2
x = (6-(-2/3*y))/2
| 4a(x+3)=4ax+12a | | 4x^3+15x^2-12x+2=0 | | 5(3x-4)+2=7(2x-3) | | tan^2(x)=1/343 | | 40*1000= | | 15x^2-16x+6=0 | | x=(y-3)-9*7 | | 3a+2=16a+48 | | 13x+1=8x+26 | | x/100=0.65 | | 2w-3w-14=0 | | x^2+2=48 | | 2w-3w=0 | | 2q-10=q-4 | | x^2-12x-57=0 | | 0=18x+10 | | y=18x+10 | | 5y-3x-4=0 | | x^2+10x+25-2x^2+2x+32=0 | | z=(x-a)/b | | 8x=-2y+8 | | -8x+15=0 | | 4a^2-4b^2+16bc-16c^2=0 | | X+3x^2=52 | | 4ln(x)=ln(81) | | 9x(-5*42)=0x | | 3y-6x+24=0 | | 9x(-5*42)=3x | | 2x[12+9]= | | -4(b-1)+2b=3(2b-1) | | 3(s+1)-(5-2)=22s | | 7k+7k=-5(8k-6)-6(k+5) |